The Impact Of Employee Separation Towards Organizational Performance -A Study On Manufacturing Industry In Malaysia - Gnanapragasam, Hari Haran (2014)
Organizational performance is vital to achieve competitive advantage, outperform than the rivalries and ensure sustainability of the business. The present research investigates the independent variables and moderating variable that could influence an organizational performance of manufacturing industry in Malaysia. Six variables were selected as independent variables and it constitute of employee knowledge, employee job satisfaction, employee commitment, employee motivation, employee productivity and survivor syndrome. Organization communication was introduced as the mediating variable.